2013
DOI: 10.1007/s00167-013-2507-y
|View full text |Cite
|
Sign up to set email alerts
|

Revision of anterior cruciate ligament reconstruction with allografts in patients younger than 40 years old: a 2 to 4 year results

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Literature reports very satisfactory results with patellar tendon allograft thanks to the bone plugs and its better adaptation into a large bone tunnel. 35 Especially in case of multiple failures and when peripheral reconstructions are needed, the use of allograft is strongly reccomended. 31,36 In our experience, we have used a prevalence of autograft BPTB and allograft as graft for the last revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports very satisfactory results with patellar tendon allograft thanks to the bone plugs and its better adaptation into a large bone tunnel. 35 Especially in case of multiple failures and when peripheral reconstructions are needed, the use of allograft is strongly reccomended. 31,36 In our experience, we have used a prevalence of autograft BPTB and allograft as graft for the last revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that revision ACL reconstruction has low-complication rates and good clinical results at both short-and midterm follow-up, with significant improvements in knee stability, patient-reported outcome scores, and patient satisfaction. 4,6,9,[23][24][25][26][27] Comparative studies, however, have consistently reported results that are inferior to primary ACL reconstruction. 5,7,8,12 Increased rates of meniscal and chondral pathology may contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Full-text articles excluded (n = 10) Reverte-Vinaixa [69] x x x Mahmoud [53] x x x Shelbourne [74] x x x Pascual-Garrido [66] x x Ventura [87] x…”
Section: Eligibility Identificationmentioning
confidence: 99%